2005
DOI: 10.1007/s00213-004-2116-z
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan depletion reduces right inferior prefrontal activation during response inhibition in fast, event-related fMRI

Abstract: These findings provide neuro-functional evidence of a serotonergic modulation of right inferior prefrontal during inhibitory motor control. The increased engagement of temporal brain regions may reflect compensatory mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
140
3
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(173 citation statements)
references
References 111 publications
28
140
3
2
Order By: Relevance
“…'*'0.10o po0.05; *po 0.05; **po 0.01; ***po0.001. (Rubia et al, 2005). These findings bear a resemblance to the current observations of and reduced activation of the dorsolateral prefrontal cortex, increased activation of the middle occipital gyrus during associative learning.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…'*'0.10o po0.05; *po 0.05; **po 0.01; ***po0.001. (Rubia et al, 2005). These findings bear a resemblance to the current observations of and reduced activation of the dorsolateral prefrontal cortex, increased activation of the middle occipital gyrus during associative learning.…”
Section: Discussionsupporting
confidence: 70%
“…Similar BOLD-effects have been observed in human ecstasy users, that is, an increased visual cortex activation after photic stimulation where the magnitude of the increase was positively related to the degree of prior ecstasy exposure (Cowan et al, 2006). In addition, there is evidence of serotonergic modulation of functional brain activity in the prefrontal cortex and limbic structures during a cognitive challenge (Evers et al, 2005;Rubia et al, 2005). In one study, acute tryptophan depletion Ecstasy and human cognitive brain function G Jager et al significantly reduced brain activation in the right orbitoinferior prefrontal cortex, whereas it increased activation in the superior and medial temporal cortex.…”
Section: Discussionsupporting
confidence: 49%
“…For example, Rubia et al (2005a) found that ATD decreased right orbito-inferior prefrontal activation in fMRI during the no-go condition, although there was no significant alteration in inhibitory performance on task. Citalopram enhanced the response of the lateral orbitofrontal cortex (BA47) to the no-go condition, whereas it attenuated the response to the no-go condition in the medial orbitofrontal (BA11), using fMRI (Del-Ben et al 2005).…”
Section: Role Of 5-ht In Action Restraintmentioning
confidence: 99%
“…Thus, studies in rats and humans have shown that manipulating 5-HT does not affect performance on tasks of inhibition that have no clear affective component, such as the stop-signal reaction-time task Cools et al, 2005;Chamberlain et al, 2006;Bari et al, 2009;Eagle et al, 2009), the self-ordered spatial working memory task (Walker et al, 2009), and the go-nogo task (Rubia et al, 2005;Evers et al, 2006) (but see LeMarquand et al, 1999).…”
Section: The Coupling Between Inhibitory and Aversive Effects Of Seromentioning
confidence: 99%